The Analysis of Student Science Literacy in Terms of Interpersonal Intelligence (Journal of Primary Education, 2019)
The purpose of this study was to describe the profile of interpersonal intelligence and science literacy through the application of Two Stay Two Stray cooperative learning model conducted in MI Miftahul Ulum 01, MI Roudlotut Tholibin, and MI Salafiyah in Kudus. This research uses mixed method with concurrent embedded research design. Technique of collecting data using pretest Literasi of Science with 10 item of description and posttest of Literasi of Science with 13 item of description and questionnaire of interpersonal intelligence. Data analysis techniques were normality test, homogeneity test, N-gain and t-test. The result of data analysis shows that there are differences in the increase of Science Literacy results from high, medium and low interpersonal intelligence ie 0.382; 0,341; and 0.192. Based on the research data, the application of Two Stay Two Stray cooperative learning model assisted by visual media can help improve the students' science literacy. The benefits of this research is to contribute thoughts to the effort to improve Literacy Science through the application of cooperative learning model Two Stay Two Stray assisted visual media in terms of interpersonal intelligence.